Loss factor measurement and indications for nonlinearities in sound insulation. Issue 1 (March 2019) - Bietz, Heinrich; Stange-Kölling, Sylvia; Schmelzer, Martin; Wittstock, Volker
The loss factor is often determined in building acoustics by measuring the structure-borne reverberation time. To do this, elements under test are excited either by a hammer or by a shaker. In several experiments with sand-lime brick walls, measured loss factors turned out to be significantly larger when hammer excitation was used instead of shaker excitation. A thorough investigation of this effect was then performed using hammer blows of different strengths and a 250-kg shaker. This way, forces are in the same order of magnitude for both excitations. Measurement results lead to the conclusion that large forces may create a nonlinear structural response. The nonlinearity is observed for a sand-lime brick wall without plastering but not for a lightweight composite wall and also not for a monolithic concrete wall. The assumption of nonlinear behaviour is furthermore supported by an additional investigation where alarm pistol shots were used to excite a sand-lime brick wall with very large airborne sound pressure levels. The airborne sound insulation of the wall turned out to be nonlinear, that is, it increased with increasing sending room levels.